Progress in Advanced Computing and Intelligent Engineering Proceedings of ICACIE 2017, Volume 2 - Panigrahi, Chhabi Rani.; Pujari, Arun K.; Misra, Sudip; Pati, Bibudhendu; Li, Kuan-Ching.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book features high-quality research papers presented at the International Conference on Advanced Computing and Intelligent Engineering (ICACIE 2017). It includes sections describing technical advances in the fields of advanced computing and intelligent engineering, which are based on the presented articles. Intended for postgraduate students and researchers working in the discipline of computer science and engineering, the proceedings also appeal to researchers in the domain of electronics as it covers hardware technologies and future communication technologies.
Secured Cloud-based Federation for EHR using Multi-Authority ABE -- A Brief Study on Build Failures in Continuous Integration: Causation and Effect -- Web Services Regression Testing through Automated Approach -- Challenges to Cloud PLM Adoption -- Evaluation of Neuropsychological Tests in Classification of Alzheimer's Disease -- Brain Tumor Classification for MR Imaging Using Support Vector Machine -- Intelligent Mobile Agent Framework for Searching popular e-Advertisements -- Medicinal Plant Information Extraction System: A Text Mining Based Approach -- Population Dynamics Indicators for Evolutionary Many-Objective Optimization -- Order Reduction of Discrete System Models Employing Mixed Conventional Techniques and Evolutionary Techniques -- MCC and Big Data Integration for Various Technological Frameworks -- Mobility Predication for Dynamic Location Area in Cellular Network Using Super Vector Regression -- Improved SLReduct Framework for Stress Detection using Mobile Phone Sensing -- A Non-autonomous Ecological Model with Some Applications -- On the Category of Quantale Semimodules.
Keywords: Signal processing; Computational intelligence; Telecommunication; Signal, Speech and Image Processing; Computational Intelligence; Communications Engineering, Networks